Clinicopathological Features of Low-Grade Appendiceal Mucinous Neoplasms Confined to the Appendix - Lu, Yiyan; Li, Fang; Ma, Ruiqing; Fang, Lan; Qi, Changhai (Frontiers in Oncology, 2021)
Objective: To investigate the clinicopathological features and follow-up of low-grade appendiceal mucinous neoplasms (LAMNs) confined to the appendix. Methods: The clinicopathological features, pathological primary tumor (pT) staging and follow-up of 22 patients with LAMNs confined to the appendix were analyzed retrospectively. Results: Of 22 patients with LAMNs, 14 were pTis (8 pTism and 6 pTisf), 6 were pT3, and 2 were pT4a. The appendiceal diameter was significantly larger for pTisf than for pTism. The interval between first symptoms and surgery was longer for pTisf than for pTism, but not significantly. No significant differences were found between the pT stages and appendiceal diameter or in the interval between the first symptoms and surgery. Pathomorphologically, the epithelial structures were mainly flat (100%), undulating or scalloped (82%); a few showed filiform villous hyperplasia (46%), and seven (32%) had serrated lesions in the background. Diverticula may be associated with LAMNs, and the location of acellular mucin caused by diverticula affected the pT stage of the LAMNs. The lack of treatment guidelines for LAMNs confined to the appendix and patients' different acceptances of preventive intervention led to varied clinical treatments. However, we found no short-term benefits of prophylactic extended resection or hyperthermic intraperitoneal chemotherapy. Conclusion: LAMNs confined to the appendix are rare and must be differentiated from serrated lesions and diverticula. LAMNs with different pT stages have inert biological behavior. Determining the long-term effects of preventive treatment on survival and recurrence requires more data and a longer follow-up.